The Biophysical Modelling of the Creation - Vincze, Janos (Jour Med Resh and Health Sci, 2023)
Euclid, who lived around 300 BC, elevated mathematics to a special status with his system of axioms; mathematics became a universal language, uninfluenced by external circumstances and human behaviour. The Euclidean contradiction was solved by János Bolyai (1802–1860): he transformed virtual Euclidean geometry into physical reality by reformulating parallelism. At the same time, he moved from the interpretation of the finite to the interpretation of the infinite, which became a key element in the scientific and theoretical models of creation, as well as in the formulation of the theory of relativity in physics and became the cornerstone of the development of astronomy. Creation goes beyond its narrow meaning, because it includes birth, life and death. There is no mercy in creation! Not from a religious or scientific point of view. Neither the scientific nor the religious understanding of creation excludes the concept of re-creation! The possibility of re-creation is a perfect parallel between the two approaches. According to both theories, we need to highlight the order. According to the Bible, human is the only species created by God in His own image.